Digital marketing and media buying of ‘Robi Axiata Ltd. – Airtel Business Unit - Amin, Layas Bin (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.